2018
DOI: 10.18632/oncotarget.25757
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori associated factors in the development of gastric cancer with special reference to the early-onset subtype

Abstract: Nowadays, gastric cancer is one of the most common neoplasms and the fourth cause of cancer-related death on the world. Regarding the age at the diagnosis it is divided into early-onset gastric carcinoma (45 years or younger) and conventional gastric cancer (older than 45). Gastric carcinomas are rarely observed in young population and rely mostly on genetic factors, therefore provide the unique model to study genetic and environmental alternations. The latest research on early-onset gastric cancer are trying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 152 publications
0
33
0
Order By: Relevance
“…The discrepancy in the severity of gastric cancer is associated with many factors and mechanisms, among which various genotypes of H. pylori strains play a role [30][31][32][33][34][35][36][37][38][39][40]. H. pylori induces other diseases of the alimentary tract, including gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue lymphoma, GERD symptoms, and dyspepsia [41][42][43][44][45][46]. There is an increasing interest in the role of H. pylori in the pathogenesis of ischemic heart disease, diabetes mellitus, and Alzheimer's disease [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in the severity of gastric cancer is associated with many factors and mechanisms, among which various genotypes of H. pylori strains play a role [30][31][32][33][34][35][36][37][38][39][40]. H. pylori induces other diseases of the alimentary tract, including gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue lymphoma, GERD symptoms, and dyspepsia [41][42][43][44][45][46]. There is an increasing interest in the role of H. pylori in the pathogenesis of ischemic heart disease, diabetes mellitus, and Alzheimer's disease [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric carcinogenesis is a complex, multifactorial process that is primarily stimulated by chronic inflammation (induced by H. pylori infection in the majority of cases); however, other processes such as the epithelial-mesenchymal transition (EMT) or intensified angiogenesis play a crucial role in GC progression [19][20][21][22][23]. Angiogenesis is a physiological process of the formation of the new blood vessels from the already existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that a high prevalence of p53 mutation might be related to genomic profiles, environmental factors, or lifestyle-related factors such as H-pylori infection, diet, sunlight, etc. in K&B province, Southwest Iran with nomadic populations and mountainous weather (47)(48)(49). Recently, some studies reported that high altitude and increased exposure to ultraviolet (UV) radiations of sunlight, (level of ultraviolet radiation increase by about 10% with every 300 m), may be related to the higher incidence rate of cancers (50,51).…”
Section: Discussionmentioning
confidence: 99%